2010
DOI: 10.1073/pnas.1007047107
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 is critical to maintain the homeostasis of the blood–testis barrier via its effects on tight junction reassembly

Abstract: In mammalian testes, the blood-testis barrier (BTB) or Sertoli cell barrier created by specialized junctions between Sertoli cells near the basement membrane confers an immunological barrier by sequestering the events of meiotic division and postmeiotic germ cell development from the systemic circulation. The BTB is constituted by coexisting tight junctions (TJs), basal ectoplasmic specializations, desmosomes, and gap junctions. Despite being one of the tightest blood-tissue barriers, the BTB has to restructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(134 citation statements)
references
References 33 publications
9
124
1
Order By: Relevance
“…In humans, BPA also reduced sperm concentration, motility and morphology (39). BPA exposure may also induce apoptosis in rat germ cells in vivo (40) and in cultured rat Sertoli cells (41), and has the potential to redistribute several known Sertoli cell junctional proteins (42,43). Subsequent studies also demonstrated that BPA is genotoxic.…”
Section: Discussionmentioning
confidence: 89%
“…In humans, BPA also reduced sperm concentration, motility and morphology (39). BPA exposure may also induce apoptosis in rat germ cells in vivo (40) and in cultured rat Sertoli cells (41), and has the potential to redistribute several known Sertoli cell junctional proteins (42,43). Subsequent studies also demonstrated that BPA is genotoxic.…”
Section: Discussionmentioning
confidence: 89%
“…Drebrin has been implicated in the regulation of cell adhesion since it was demonstrated to stabilize connexin 43 (Cx43)-containing GJ plaques, possibly serving as an adaptor of the actin cytoskeleton 49 by recruiting or modulating the activity of other actin regulatory proteins, such as Esp8 and the Arp2/3 complex, which confer actin filament bundling and branching, respectively. 15,[50][51][52][53] Cx43 was shown recently to be involved in junction restructuring at the BTB, particularly in the reassembly of the TJ-barrier following its disruption, 38,54 which occurs during the transit of preleptotene spermatocytes at stage VIII of the epithelial cycle. Thus, it was tempting to speculate that drebrin E is participating in these events by recruiting actin regulatory proteins, such as Arp3 to the apical and/or the basal ES since Arp3 was shown to be a binding partner of drebrin E as demonstrated herein.…”
Section: Discussionmentioning
confidence: 99%
“…Also, at this cell density, ultrastructures of tJ, basal eS, desmosome, and GJ were detected at the Sertoli-Sertoli cell interface under electron microscopy, illustrating functional junctions were established in these cell epithelia as detailed elsewhere. 38,54,77 It was noted that in the control Sertoli cells, F-actin formed an extensive network of filaments, which was used to maintain proper cell shape. Drebrin e was detected at the Sertoli-Sertoli cell interface (see "yellow" arrowheads in middle column) and in the cell cytosol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mammalian testis, immunohistochemistry and hybridization histochemical studies have demonstrated that Cx43 participates in the formation of homocellular gap junctions between adjacent Sertoli cells, and the heterocellular gap junction between Sertoli cells and spermatogonia or spermatocytes [Li et al 2010;Palmiero et al 2003;Tan et al 1996]. With regard to our results, immunostaining for Cx43 showed that the distribution and expression of the Cx43 protein were different in the seminiferous tubule ( Figure 1A-C).…”
Section: Pd20 Are Shown Inmentioning
confidence: 57%